What affects sustainable coworking behavior: A psychological ownership perspective - Dastoornikoo, Nika (My University, 2023)
Coworking spaces, especially after the pandemic, have been widely welcomed. Along with this, the issue of sustainability and sustainable behavior has become an increasingly important issue. The aim of this study is to identify the factors that can affect the sustainable behavior of coworking members. Previous studies in coworking spaces have paid attention to the role of design and furniture, or the owner, in creating and maintaining sustainability in these spaces. In line with Magnusson et al. (2022), this study assumes that: 1) members can significantly contribute to creating sustainability in the coworking space and 2) sustainable coworking behavior (SCB) should include all three aspects: self, others, and the planet. This study aimed to identify potential, influential factors in coworking spaces. The theory of psychological ownership (PO) was employed to achieve this goal. This particular theoretical framework was chosen due to its alignment with the sharing economy concept, a prominent feature of coworking spaces. Additionally, from a psychological perspective, PO has been shown to influence human behavior, including sustainable behavior. As such, it is deemed a suitable lens to explore factors affecting behavior in coworking spaces.By reviewing the literature, it was shown that this theory could be a good candidate for explaining all three aspects of the sustainable behavior of members in the coworking space - productivity (self), prosociality (others), and responsibility (planet). Finally, a contextualized scale is proposed to help measure members' psychological ownership in the coworking space.
Keywords: Coworking Space; Psychological ownership; Sustainable coworking behavior; Productivity; Prosociality; Responsibility; Scale contextualization